Effectiveness of Socialization Through PowerPoint Media to Understanding Nutrition of Adolescents - Taufik Firman; Asep Bayu Dani Nandiyanto (ASEAN Journal of Science and Engineering Education, 2023)
The purpose of this study is explaining how the effectiveness of socialization through PowerPoint media and to describe the effect of socialization on adolescent knowledge about adolescent nutrition fulfillment. Fulfillment of nutrition is something important in adolescence because at this time the physical growth of humans is very rapid, therefore knowledge and fulfillment of nutrition in adolescents is very necessary for optimal human growth. The method used in this research is a quantitative approach with an experimental research design. The results socialization generally has a positive impact on increasing the understanding of the employees of the Village of Employees towards the fulfillment of adolescent nutrition, which is seen by the increase in knowledge seen from the increased average value of the pre-test and post-test. However, this increase is not significant and is considered ineffective with the N-Gain calculation. One of the causes of the ineffectiveness of socialization is the limited time and the display on PowerPoint is less attractive and monotonous. This research is expected to be a reference for the preparation of optimal socialization with the selection of media and its design as well as increasing public understanding of the fulfillment of adolescent nutrition.